What do simple short-term models say about the latest economic trends in Russia? - Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2025)
We consider the applicability of simple statistical models to Russia's short-term economic trends in a wartime context. We develop several composite indicators combining economic variables to predict Russian GDP trends both before and after the invasion if Ukraine in 2022. In addition, our SVAR model estimations highlight the exceptionality of wartime. Russia's actual GDP performance in 2022 is considerably weaker than predicted by our model. The situation then reverses in 2023 and particularly at end-2024 the GDP outperforms model predictions.
urn:nbn:fi-fe2025051444244
Keywords: 330; Russian economy; statistics; principal component analysis; SVAR